The Open Language Archives Community: a 20-year update. Issue 5 (23rd November 2022) - Bird, Steven; Simons, Gary F.
Abstract : Purpose: This paper reports on the first 20 years of the Open Language Archives Community (OLAC), comprehensive infrastructure for indexing and discovering language resources. Design/methodology/approach: We begin with the original vision, assess progress relative to the original requirements, and identify ongoing challenges. Findings: Based on the overview of OLAC history and recent developments and on the analysis of the situation in the language archives area as a whole, the authors propose an agenda for a more sustainable future for open language archiving. Originality/value: This paper examines the progress of OLAC and discusses improvements in such areas as participation, access, and sustainability.